Assessing food safety knowledge, attitude and practices of catering services in Long An Province, Vietnam - Giang Hoang Huynh; Loc Thai Nguyen; Anal, Anil Kumar; Kuwornu, John K.M.; Sadiq, Muhammad Bilal; Department of Home Affaire, Long An Province, Vietnam (Pathum Thani, Thailand : Asian Institute of Technology, 2018)
The main objectiveof this study was aimed to judge food safety knowledge, attitude and practices amongstcatering services handlers in Long An province.The questionnaire was used to conduct a cross-sectional study of 751 food handlers in catering services from seven main districts in Long An province.All respondents were collected socio-demographic information.Questionsofknowledge on food safety (i.e. foodborne pathogens, practices in food preparation, contamination of food sources) and food safety attitude & practices were evaluated. The compiled data was analyzed by one-way ANOVA. Overall, catering services food handlers had moderate level of knowledge and good level of attitude & practices on food safety.Between participants' food safety knowledge,attitude & practices and social demographicwereobserved significant effects(exception for the age factor) that showed significant associations in this study. Food handlers had average on food safety knowledge (M = 80.08%, SD = 11.56) with high knowledge on food safety attitude and practices (M = 89.84%, SD = 20.76; M = 87.88, SD = 23.03). Multiple regression binary logistic analyses divulged that presence at food safety training courses was a significant and independent forecaster of the participants{u2019} food safety knowledge, attitude and practices. Theresults of studyhighlighted problemswith regards to the proportionsof food safety knowledge acquisition by catering services food handlers. As a result, this insures ameliorations not only in the better strategiesof management modules but also has a comprehensive view for the respective authorities.
A thesis submitted in partial fulfillment of the requirements for thedegree of Master of Science inFood Engineering and Bioprocess Technology, School of Environment, Resources and Development
Thesis (M. Sc.) - Asian Institute of Technology, 2018
Keywords: Food -- Safety measures; Caterers and catering -- Vietnam